The influence of 6-Benzylaminopurine (BAP) on yield responses and photosynthetic physiological indices of soybean - Xinglong Lian; Shuang Liu; Aatika Sikandar; Zongli Kang; Yaxing Feng; Lanyuwen Jiang; Yuanyuan Wang (Kuwait Journal of Science)
Soybean plants produce a large number of flower buds. However, the majority of them do not become pods and die during development. The bulk of total reproductive abscission is caused by flower and pod drop, or abortion, which impacts prospective soybean yield. Plant growth regulators serve critical functions in plant development, but only recently have their tasks been recognized in the manifestation of yield components, product, and seed qualities in soybean. The objectives of this study were to see how different concentrations of 6-Benzylaminopurine (BAP) affected photosynthetic physiological indexes, as well as gene expression of chlorophyll synthesis at the transcript level in soybean plants. In the current investigation, spraying different concentrations of BAP had no significant effect on the soybean yield. However, the BAP generated significant alterations in chlorophyll content as compared to the control. Consequently, the use of BAP significantly boosted the net photosynthetic rate. Furthermore, the current study found that BAP significantly influenced stomatal conductance and net transpiration compared to the control plant. The application of BAP significantly improves the expression of all genes that encode for chlorophyll biosynthesis. The expression of genes in leaves exhibited more up-regulation as compared to the stem. In general, this work offers a new and better understanding of how BAP might be employed to boost yield and chlorophyll biosynthesis.